A spatial data warehouse to predict megaliths slabs sources: mixing geochemistry, petrology, cartography and archaeology for spatial analysis - Nogueira, P. (2015)
MEGAGEO - Moving megaliths in the Neolithic is a project that aims to find the provenance of slabs used in the construction of dolmens. A multidisciplinary approach has been carried out with researchers from the several fields of knowledge involved. In this work it is presented a spatial data warehouse specially developed for the project, which comprises information from national archaeological databases, geographic and geological information and new geochemical and petrographic data obtained during the project. Redondo area is used as a case study for the application of the spatial data warehouse to analyze relationships between geochemistry, geology and the dolmens of the region.